Affective and enjoyment responses in high intensity interval training and continuous training: A systematic review and meta-analysis. - Bruno Ribeiro Ramalho Oliveira; Tony Meireles Santos; Marcus Kilpatrick; Flávio Oliveira Pires; Andréa Camaz Deslandes (PLoS ONE)
Previous studies investigating the effects of high intensity interval training (HIIT) and moderate intensity continuous training (MICT) showed controversial results. The aim of the present study was to systematically review the literature on the effects of HIIT and MICT on affective and enjoyment responses. The PRISMA Statement and the Cochrane recommendation were used to perform this systematic review and the database search was performed using PubMed, Scopus, ISI Web of Knowledge, PsycINFO, and SPORTDiscus. Eight studies investigating the acute affective and enjoyment responses on HIIT and MICT were included in the present systematic review. The standardized mean difference (SMD) was calculated for Feeling Scale (FS), Physical Activity Enjoyment Scale (PACES) and Exercise Enjoyment Scale (EES). The MICT was used as the reference condition. The overall results showed similar beneficial effects of HIIT on PACES and EES responses compared to MICT with SMDs classified as small (PACES-SMD = 0.49, I2 = 69.3%, p = 0.001; EES-SMD = 0.48, I2 = 24.1%, p = 0.245) while for FS, the overall result showed a trivial effect (FS-SMD = 0.19, I2 = 78.9%, p<0.001). Most of the comparisons performed presented positive effects for HIIT. For the FS, six of 12 comparisons showed beneficial effects for HIIT involving normal weight and overweight-to-obese populations. For PACES, six of 10 comparisons showed beneficial effects for HIIT involving normal weight and overweight-to-obese populations. For EES, six of seven comparisons showed beneficial effects for HIIT also involving normal weight and overweight-to-obese populations. Based on the results of the present study, it is possible to conclude that HIIT exercise may be a viable strategy for obtaining positive psychological responses. Although HIIT exercise may be recommended for obtaining positive psychological responses, chronic studies should clarify the applicability of HIIT for exercise adherence.